POTENSI DAN MODEL PENGEMBANGAN INDUSTRI MANUFAKTUR DI KOTA MALANG - Ida Nuraini (Jurnal Gamma, 2013)
POTENSI DAN MODEL PENGEMBANGAN INDUSTRI MANUFAKTUR DI KOTA MALANGModel Development Potential and Manufacturing Industry in MalangIda Nuraini Jurusan Ekonomi Pembangunan, Fakultas Ekonomi dan BisnisUniversitas Muhammadiyah Malang nurainiida@yahoo.comABSTRACTThe results of an analysis of the potential map of Malang industrial sector, showed the following results: (a) the furniture industry in Malang are mostly concentrated in the District Blimbing. (b) pottery and ceramics industries is concentrated in District Sukun and Lowokwaru. (c) industry and the car body repair shops are concentrated in the District Blimbing and Klojen. (d) the handicraft industry is concentrated in District Blimbing and Sukun. (e) the chemical industry is concentrated in District Blimbing and Sukun. (f) the metal industry is mostly concentrated in the District of Sukun and Klojen. (g) the food and beverage industry is concentrated in District Klojen and Sukun. (h) the furniture industry, textile printing and concentrated in District Blimbing and Klojen (i) the tobacco industry is concentrated in District Kedungkandang and Sukun. Based on the analysis results show that the competitiveness of the food and beverage industry Malang has a comparative advantage compared Malang, Batu and East Java Province. While the results of the analysis of the factors influencing the growth of the industrial sector, the results indicate that capital, the value of raw materials and value-added positive effect on manufacturing production variables. As for the variable labor negatively affect production.Key wood : Manufacturing industry, the potential of the industrial sector, Malang City.ABSTRAKHasil analisis peta potensi sektor industri Malang, menunjukkan hasil sebagai berikut: (a) industri mebel di Malang sebagian besar terkonsentrasi di Kabupaten Blimbing. (b) tembikar dan keramik industri terkonsentrasi di Kecamatan Sukun dan Lowokwaru. (c) industri dan perbaikan bodi mobil toko terkonsentrasi di Kecamatan Blimbing dan Klojen. (d) industri kerajinan terkonsentrasi di Kecamatan Blimbing dan sukun. (e) industri kimia terkonsentrasi di Kecamatan Blimbing dan sukun. (f) industri logam sebagian besar terkonsentrasi di Kecamatan Sukun dan Klojen. (g) industri makanan dan minuman terkonsentrasi di Kecamatan Klojen dan sukun. (h) industri mebel, pencetakan tekstil dan terkonsentrasi di Kecamatan Blimbing dan Klojen (i) industri tembakau terkonsentrasi di Kecamatan Kedungkandang dan sukun. Berdasarkan analisis hasil menunjukkan bahwa daya saing industri makanan dan minuman Malang memiliki keunggulan komparatif dibandingkan Malang, Batu dan Provinsi Jawa Timur. Sedangkan hasil analisis faktor yang mempengaruhi pertumbuhan sektor industri, hasil menunjukkan bahwa modal, nilai bahan baku dan nilai tambah efek positif pada manufaktur variabel produksi. Adapun tenaga kerja variabel negatif mempengaruhi produksi.Kata kunci: Manufaktur industri, potensi sektor industri, Kota Malang